Exploring Graduate Students' Practices of Writing for Scholarly Publication - Masyhudi Lathif; Joko Nurkamto; Diah Kristina (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2022)
The demand of writing for scholarly publication as a part of graduation requirements has now been apparent in many graduate programs. The present study attempted to discover the English Language Teaching (ELT) graduate students’ practices in writing for scholarly publication. This present study employed case study to further disclose the graduate students’ perceived discursive and non-discursive constraints as well as the way they learn how to write for scholarly publication. To collect the data, a synchronous interview session was conducted to two ELT master’s students from a state university in Central Java, Indonesia. Drawing on the theory of discourse community and legitimate peripheral participation, the participants challenges and learning process of learning process were scrutinized. It is expected that this study provides new insights for policy making in a postgraduate context and for the teaching of EAP to support writing for scholarly publication.